SCHOOL FEEDING PROGRAM USING RICE-PEA BEVERAGE IN SOME PRIMARY SCHOOLS: DOES IT HAVE BENEFIT? - Satoto, Satoto; Rahfiluddin, Z; Sakti, H (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2005)
ABSTRACT School feeding program is believed to be one effort among others to improve attendance rate, nutritional status and cognitive function of school children, which in turn improve academic performance of them. A study was conducted to evaluate a school feeding program using rice-pea beverage in Bandung, Indonesia. Its objective is to measure effect of the program on attendance rate, nutritional status, cognitive function and academic performance of the children joining the program. A control group design was administered. A number of students of class 3,4 and 5 from schools joining the feeding program were selected as program group, and more or less same number of school children in other schools with similar socio-economic situation were selected as control group. The feeding program was organized for 6 months. Attendance rate was measured by number of absentees, total and due to sickness in one semester. Nutritional status was standardized using WHO-NCHS z-score for weight-for-age (WAZ) and height-for-age (HAZ). Cognitive function was measured by Coloured Progressive Matrices (CPM), and score of Mathematics and Indonesian Language (Bahasa Indonesia) were measured using specific scholastic testings. School and home learning environment, certain food consumption frequencies were collected as covariates. GLM analyses were administered. The study found that after being controlled by some covariates, at the end of the study children in the program group showed better attendance rate, nutritional status, cognitive function and school performance. It is assumed that the improvement was due to better attendance rate as the program attracted the children to attend more days in the schools and due to improvement of food consumption provided by the program and at home. More in-depth, more specific and longer study, administering randomized case-control trial is recommended. Comparison of the use of foodstuffs for the purpose is also interesting to be studied. Permalink : http://ejournal.undip.ac.id/index.php/jgi/article/view/3239